Dynamic interconnectedness of economic confidence, energy prices, and interest rates: Insights from the euro area - ARZOVA, SABRİ BURAK (My University, 2024)
This work examines the time-varying interlinkages among economic confidence, energy prices, geopolitical stress, and short/long-term interest rates in the Euro Area. Our research meticulously explores the interplay between economic confidence and various determinants, including financial indicators, geopolitical stress incidents, and energy prices. Employing innovative approaches such as the time-varying parameter vector autoregression (TVP-VAR) time and frequency-domain connectedness, we uncover the nuanced relationships between economic confidence, financial indicators, and energy prices. We illuminate the systemic nature of shock transmission in the Euro Area, identifying key net transmitters and recipients of shocks, with short-term interconnectedness emerging as a dominant feature, especially during pivotal events such as the global financial crisis, the COVID-19 pandemic, and geopolitical conflicts. Our empirical findings can be summarized as follows: First, both the time and frequency-domain connectedness indexes correctly associate with major financial/geopolitical events. Second, BCI and CCI respond to the GFC asymmetrically. Third, Brent and short/long-term interest rates are the net transmitters of shocks on average. Fourth, there is a considerable augmentation in return spillovers during the period characterized by the pandemic crisis compared to the GFC. Finally, our findings for frequency-dependent connectedness networks indicate that the market is particularly susceptible to short-term shocks. This study has significant ramifications for investors, market players, and policymakers.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Çalışma Ekonomisi ve Endüstri ilişkileri; Çalışma Ekonomisi; Social Sciences and Humanities; Economics; Labor Economics and Industrial Relations; Labor Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; İŞ FİNANSI; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; BUSINESS, FINANCE; Finans; Sosyal Bilimler ve Beşeri Bilimler; Ekonomi ve Ekonometri; Finance; Social Sciences & Humanities; Economics and Econometrics; Economic confidence; Energy prices; Frequency-dependent connectedness networks; Network analysis TVP-VAR connectedness; Energy prices; Economic confidence; Network analysis TVP-VAR connectedness; Frequency-dependent connectedness networks